The Role of the Sound of the Letter "Q" in the Middle and End of Words in Mandar - Nabilah Haruna; Cece Sobarna; Wahya wahya (Journal of Social Research, 2024)
This study raises the role of the sound of the letter "q" in Mandar, especially when it is in the middle and end of the word. The Mandar language, which lives and is used by the people of West Sulawesi, has characteristics that are often misunderstood by non-Mandar speakers. One of the most common mistakes is to replace the sound of the letter "q", which is actually a glottal stop, with the sound of "k", which results in a significant shift in meaning. This study aims to reveal the importance of correct understanding of the pronunciation of glottal stops, especially in the context of the Mandar language. Through a qualitative descriptive method, this study collected data from native speakers and the Great Dictionary of Mandarin-Indonesian Language, to analyze words containing the letter "q". The results of the study show that the sound of glottal stop is very crucial in maintaining the authenticity of the meaning and understanding of a word in Mandar. With a collection of 55 words, the study highlights the urgency of preserving the correct way of pronunciation to avoid misunderstandings among non-native speakers. This research not only contributes to the development of linguistics, but also supports efforts to revitalize the Mandar language, which is now endangered. By understanding the sound of this glottal stop, it is hoped that news anchors, journalists, and the general public can better appreciate and use the Mandar language appropriately, so that this regional language remains alive and developing.